(Re)inserção social de consumidores de crack: percepção da autoeficácia e do suporte sociofamiliar. - Melo, Paulo de Tarso Monteiro de Albuquerque (2019)
Based on the premise that the excessive consumption of drugs, especially crack, can cause severe problems through social isolation, fights, rupture of family ties, unemployment, among other conflicts, the efforts are sustained in the attempt to rescue the aspects of basic human rights in the life processes of these people. Therefore, several of the care actions include in their therapeutical proposals the social (re)insertion as a way to contribute to overcoming these problems. The objective of this study was to investigate the perception of the crack user about self-efficacy, family and society support and their social (re)insertion. The theoretical reflection was based on the Social Cognitive Theory and on contemporary authors who contributed to the theme. The adopted outline was mixed and cross-sectional, initially performing the quantitative phase and, subsequently, the qualitative phase. The data was collected in two intensive accommodation centers of a social assistance program in Pernambuco. 56 male crack users who met the inclusion criteria during the screening conducted by two instruments participated in the survey. Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) and the MiniMental State Examination – MMSE. For the research, two instruments were used: ABIPEME scale, the Perception of Family Support Inventory - (IPSF), the Saranson's Social Support Questionnaire (SSQ), the General Self-Efficacy Scale (GSE) and a triggering question about social reinsertion. The analysis of the results was performed in two phases: the first - quantitative, brought the socioeconomic profile of the 56 crack users, followed by the descriptive analysis of the perception of social support, family support, and self-efficacy. In continuity, the qualitative part presented the thematic content analysis, performed from the data obtained during the interview with 45 among these crack users. The average age of the participants was 32 years old (SD = 7.67), ranging from 18 to 53 years. The majority had completed basic education (35.71%). Almost all users didn’t have established relationship (89,29%) and the majority (48.21%) lived with people they considered to be friends or colleagues. Most of them reported that they had no religion (35.71%) and among those who reported having some religion, only 25% admitted being practitioner. Regarding the socioeconomic profile, the participants were predominantly from C class (64.29%). In terms of Social Support, the overallsatisfaction average was 137.88 (SD = 23.64), indicating a medium-low support perception. The total score obtained in the IPSF was 51,30 (SD = 15.15), indicating a low perception of family support. On the other hand, in EAGP, the average score of selfefficacy perception was 27,55 (SD = 3.72), consisting a medium-high perception. In the qualitative analysis, it was possible to think about a perception of social reinsertion focused on four meaning nuclei, namely: “work, family and stop using drugs”; “rescue of citizenship (rights and duties); “does not believe in social reinsertion” and “the social reinsertion depends on the society” (opportunities). In this study, we were able to consider the social (re)insertion in perspective as in a spectrum in which it can be understood as the final objective, but built in a continuum of actions in favor of a better quality of life of crack users. As a result of this reflection, we hope the findings discussed here can refine the curiosity of the professionals for the theme while contributing to important information for the training of those working in the field.